2013
DOI: 10.1530/joe-13-0160
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation exacerbates glucose metabolism disorders in C57BL/6J mice fed with high-fat diet

Abstract: Inflammatory stress is closely related to metabolic disease and insulin resistance. The precise cellular mechanism linking obesity and diabetes is largely unknown, but about 14-20% of obese individuals develop diabetes. In this study, we investigated whether chronic inflammation exacerbated glucose metabolism disorder by impairing b cell function in high-fat diet (HFD)-fed C57BL/6J mice. We used s.c. casein injection to induce chronic inflammation in HFD-fed C57BL/6J mice; 14 weeks on a HFD resulted in weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 32 publications
7
23
0
Order By: Relevance
“…Increase in islets mass, which begins early in HFD exposure, coincident with the onset of hyperglycemia and glucose intolerance, but before the onset of insulin resistance has been reported (Stamateris et al, ). Therefore, the higher increase in insulin secretion in response to glucose load in HFD mice may be correlate with increased pancreatic beta cell mass, consistent with previous study (Collins et al, ; Fraulob et al, ; Li et al, ; Wu et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Increase in islets mass, which begins early in HFD exposure, coincident with the onset of hyperglycemia and glucose intolerance, but before the onset of insulin resistance has been reported (Stamateris et al, ). Therefore, the higher increase in insulin secretion in response to glucose load in HFD mice may be correlate with increased pancreatic beta cell mass, consistent with previous study (Collins et al, ; Fraulob et al, ; Li et al, ; Wu et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Obesity-induced chronic inflammation is triggered by metabolic signals such as excess nutrients, and involves inflammatory responses originated within metabolic cells such as adipocytes, hepatocytes or myocytes, resulting in damage to metabolic homeostasis with insulin resistance1617183642535455. In agreement with these studies, we have previously found activated NFkB pathway and increased expression of pro-inflammatory genes in insulin resistant myotubes derived from diabetic-obese subjects, but not in insulin sensitive myotubes derived from non-diabetic-lean subjects56.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies using obese models have shown increased inflammation to be associated with changes in glucose metabolism (41,67). In this study, obesity was also associated with a downregulation of ovarian glucose transporter gene expression (GLUT4 and GLUT9) compared with lean controls.…”
Section: Discussionsupporting
confidence: 50%